A Carboxymethyl Chitosan‐Based Double‐Crosslinking Hydrogel with Enhanced Antibacterial Properties for Accelerated Wound Healing. Issue 8 (18th May 2022) - Mo, Xinya; Huang, Wen‐Can; Sun, Shifeng; Chi, Zhe; Ding, Yuanyuan; Mao, Xiangzhao
Abstract: Here, a novel double‐crosslinked hydrogel dressing with enhanced antibacterial and anti‐inflammatory activities is reported. Carboxymethyl chitosan is crosslinked with silane and Ca 2+ to form a double‐crosslinked hydrogel, and silver nanoparticles are loaded to introduce antibacterial properties to the hydrogel. The covalent crosslinking preserves the integrity of the hydrogel matrix, while the ionic crosslinking dissipates the energy under deformation. It combines high stretchability, toughness, tissue adhesion, and antimicrobial function. This hydrogel exhibits excellent cytocompatibility and hemocompatibility. Moreover, in vitro and in vivo investigations demonstrate its efficacy in accelerating bacterial‐infected wound healing. Given its excellent cytocompatibility and mechanical properties, this hydrogel is anticipated to be widely used in bacteria‐associated wound management. Abstract : A carboxymethyl chitosan‐based double‐crosslinking hydrogel dressing for accelerated wound healing is developed. In vitro and in vivo experiments demonstrate that the hydrogel has stretchability, tissue adhesion, antimicrobial functions, and exhibits excellent cytocompatibility and hemocompatibility. This hydrogel is anticipated to be widely used in bacteria‐associated wound management.